2017
DOI: 10.1007/s10928-017-9543-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative modeling of the dynamics and intracellular trafficking of far-red light-activatable prodrugs: implications in stimuli-responsive drug delivery system

Abstract: The combination of photodynamic therapy (PDT) with anti-tumor agents is a complimentary strategy to treat local cancers. We developed a unique photosensitizer (PS)-conjugated paclitaxel (PTX) prodrug in which a PS is excited by near-infrared wavelength light to site-specifically release PTX while generating singlet oxygen (SO) to effectively kill cancer cells with both PTX and SO. The aim of the present study was to identify the determinants influencing the combined efficacy of this light-activatable prodrug, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
0
8
0
1
Order By: Relevance
“…121,122 Coined "photo-unclick chemistry", the activation mechanism is identical to the one shown in Scheme 4. In a series of publications, [122][123][124][125][126][127][128][129][130] You and co-workers described photodynamic prodrugs containing the aminoacrylate linker and the tubulin polymerization inhibitor combretastatin A-4 (CA4). In combination with the pro-PS iodo-substituted 5IJ6)carboxyfluorescein diacetate (CF), the cascade, dual-activation photodynamic prodrug 63 was developed to facilitate easier handling under ambient light (Table 7).…”
Section: Vinyl Heteroatom-based Linkersmentioning
confidence: 99%
See 1 more Smart Citation
“…121,122 Coined "photo-unclick chemistry", the activation mechanism is identical to the one shown in Scheme 4. In a series of publications, [122][123][124][125][126][127][128][129][130] You and co-workers described photodynamic prodrugs containing the aminoacrylate linker and the tubulin polymerization inhibitor combretastatin A-4 (CA4). In combination with the pro-PS iodo-substituted 5IJ6)carboxyfluorescein diacetate (CF), the cascade, dual-activation photodynamic prodrug 63 was developed to facilitate easier handling under ambient light (Table 7).…”
Section: Vinyl Heteroatom-based Linkersmentioning
confidence: 99%
“…Similar Pc-based constructs with the anticancer agent paclitaxel (PTX) were also synthesized showing the feasibility of using the linker with secondary alcohols and not only phenolics. 127,128,130 Recently, You and co-workers developed the mitochondriatargeting prodrug 67 based on an intermolecular prodrug/PS system. 132 The prodrug was assembled from CA4, an AA linker, and the targeting ligand Rhodamine B (RhB).…”
Section: Vinyl Heteroatom-based Linkersmentioning
confidence: 99%
“…Woo and co‐workers developed a prodrug of paclitaxel based on a silicon‐containing porphyrin macrocycle, which was activated by red light due to 1 O 2 production. The drug molecule was covalently linked to the silicon core and could be simply cleaved after oxidation.…”
Section: Ros‐activated Drug Delivery and Small‐molecular Prodrug Systemsmentioning
confidence: 99%
“…In our lab, we chose the Pc-(L-PTX) 2 (entry 8) prodrug to begin our in vitro investigation based on a QSP approach (Figure 9) [82]. We found that around 80% of our prodrug formed aggregates in medium, due to its high lipophilicity.…”
Section: In Vitro Efficacy Evaluation Of Prodrugs Guided By Quantitatmentioning
confidence: 99%
“…The model components describing the kinetic and dynamic processes of the released paclitaxel (PTX) (blue arrows) only apply to the cleavable Pc-(L-PTX)2 . Reproduced with permission from[82].…”
mentioning
confidence: 99%